2013
DOI: 10.3168/jds.2013-6833
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for claw disorders and the effect of preselecting cows for trimming

Abstract: Claw disorders are important traits relevant to dairy cattle breeding from an economical and welfare point of view. Selection for reduced claw disorders can be based on hoof trimmer records. Typically, not all cows in a herd are trimmed. Our objectives were to estimate heritabilities and genetic correlations for claw disorders and investigate the effect of selecting cows for trimming. The data set contained 50,238 cows, of which 20,474 cows had at least one claw trimming record, with a total of 29,994 records.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
(56 reference statements)
3
24
1
3
Order By: Relevance
“…Variance Components. Heritability estimates for the hoof health traits considered in the present study were generally higher than previously reported in other dairy cow populations that also used linear models and considered the same noninfectious and different infectious hoof health traits (van der Waaij et al, 2005;van der Linde et al, 2010;Johansson et al, 2011;van der Spek et al, 2013), the reason for which is likely multifactorial. First, participating herds in the present study were selected because of their reputation for prompt and correct data recording, thus helping to reduce the residual variance.…”
Section: Hoof Health Traitscontrasting
confidence: 70%
See 1 more Smart Citation
“…Variance Components. Heritability estimates for the hoof health traits considered in the present study were generally higher than previously reported in other dairy cow populations that also used linear models and considered the same noninfectious and different infectious hoof health traits (van der Waaij et al, 2005;van der Linde et al, 2010;Johansson et al, 2011;van der Spek et al, 2013), the reason for which is likely multifactorial. First, participating herds in the present study were selected because of their reputation for prompt and correct data recording, thus helping to reduce the residual variance.…”
Section: Hoof Health Traitscontrasting
confidence: 70%
“…Moreover, differences in relative economic importance (Enting et al, 1997;Ettema and Østergaard, 2006) and control methods (Leach et al, 2010;Bicalho and Oikonomou, 2013) for hoof health traits exist in different environments and production systems. All herds in the present study were pasture-based, spring-calving production systems; many other studies (Chapinal et al, 2013;Oberbauer et al, 2013;van der Spek et al, 2013) have documented variance components of hoof health traits from cows in confinement, nonseasonal calving herds. Genotype × environment interactions are known to contribute to differences in the genetic variances among production systems, a phenomenon that has been reported for other performance traits in dairy cattle (Berry et al, 2003;Nauta et al, 2006;Haile-Mariam et al, 2008).…”
Section: Hoof Health Traitsmentioning
confidence: 95%
“…The production decline will usually occur during two to four months before the claw disease is diagnosed (Strapák et al, 2013). For example in Netherlands, the economic loss due to the claw disorders have been estimated at 75 $ per cow per year (Bruijnis et al, 2010;Van der Spek et al, 2013). Krupová et al (2016) estimated the marginal economic value of claw disorders incidence in dairy population of Slovak Pinzgau cattle to −€26.73 per case per cow and year.…”
Section: Introductionmentioning
confidence: 99%
“…For European dairy cattle the prevalence of 70% of the cows with at least one claw disorders have been reported (Van der Linde et al, 2010;Chapinal et al, 2013;Van der Spek et al, 2013). The risk of claw disorders incidence depends on various factors, including environment conditions (for example management practices and design of the facilities) and animals' genetic background (Cramer et al, 2009;Van der Linde et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation